2021
DOI: 10.15244/pjoes/124118
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Mutual Feedback Relationship between Extreme Drought and Flood Events and Ecological Succession of Vegetation

Abstract: In the context of climate change, the extreme precipitation events over most of the mid-latitude land masses and over wet tropical regions will very likely become more intense and more frequent, which may cause increases in the intensity and frequency of extreme drought or flood events. To explore the mechanism of dynamic and functional changes in ecosystems driven by extreme drought and flood events (EDFEs) in the future and the interaction between the two, this study focuses on the mutual feedback relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Droughts and floods, with their broad impact and frequent occurrence, post significant threats to the ecological environment, food security, economic development, and human health [1][2][3][4]. Under changing environments, drought and flood disasters with spatiotemporal correlation will occur continuously or interact with each other to develop into dry and wet combination events (DWCEs) [5,6], increasing the scope and intensity of the disaster and causing more serious losses to society.…”
Section: Introductionmentioning
confidence: 99%
“…Droughts and floods, with their broad impact and frequent occurrence, post significant threats to the ecological environment, food security, economic development, and human health [1][2][3][4]. Under changing environments, drought and flood disasters with spatiotemporal correlation will occur continuously or interact with each other to develop into dry and wet combination events (DWCEs) [5,6], increasing the scope and intensity of the disaster and causing more serious losses to society.…”
Section: Introductionmentioning
confidence: 99%
“…However, the increased frequency and duration of flooding events due to changes in land use patterns, climate change-induced extreme weather, and regime alterations stemming from reservoir and weir development within a floodplain can disrupt the soil environment by introducing contaminants [14]. Physical disturbances in an ecosystem also affect the succession of vegetation [15]. Previous studies have demonstrated that such extreme drought and flooding related soil disturbances affect succession through vegetation growth and survival [15].…”
Section: Introductionmentioning
confidence: 99%
“…Physical disturbances in an ecosystem also affect the succession of vegetation [15]. Previous studies have demonstrated that such extreme drought and flooding related soil disturbances affect succession through vegetation growth and survival [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it directly affects vertical hydrological processes such as the atmospheric water vapor flux (Fathizadeh et al, 2017;Ghimire et al, 2017;Liu J. et al, 2018b), soil water movement (Wu et al, 2017;Huang et al, 2017;Yu et al, 2018;Bo et al, 2021;Xu M. et al, 2021), and evapotranspiration (Li et al, 2016;Wang et al, 2018). On the other hand, the canopy structure and community succession of vegetation indirectly affect the horizontal hydrological processes such as runoff generation and confluence on the slope (Amenu and Kumar, 2008;Yang et al, 2010;Dong et al, 2021) by changing the underlying surface conditions and the surface roughness. Aiming at mitigating the extreme impacts of climate change on hydrological processes and improving ecological service functions, how to optimally allocate ecological restoration on slopes has become one of the key scientific issues in the intersecting fields of climatology, ecology, and hydrology.…”
Section: Introductionmentioning
confidence: 99%